Mastering your fellowship (Online) - Klaus B von Pressentin; Mergan Naidoo; Andrew Ross; Tasleem Ras (South African Family Practice)
The series, “Mastering your Fellowship”, provides examples of the question format encountered in the written examination, Part A of the FCFP (SA) examination. The series is aimed at helping family medicine registrars prepare for this examination. Model answers are available online.